El contexto internacional y las exportaciones peruanas de productos agropecuarios no tradicionales: 1990-2010 - León Mendoza, Juan (2010)
The article aims to understand and estimate the influence of development of the international context, especially China’s economic growth, on the large positive performance of exports of Peru´s nontraditional agriculture products in the 1990- 2010 period. In the context of an economic model, econometric regressions made show that China’s economic growth has lead to increases in imports, therefore in the demand and international prices, which has contributed to the growth of Peruvian agricultural exports. The elasticity of the income of demand estimated that for every increase of 1% of Chinese GDP, exports of nontraditional agriculture products in Peru grew by 1,3%, approximately.